Jarl Sigvaldi and the battle of Svoldr in saga tradition - Morawiec, Jakub (Folia Scandinavica Posnaniensia, 2009)
The battle of Svoldr is one of the most outstanding moments in saga tradition, which preserves memory about Viking Age Scandinavia. The fame of the battle was strictly connected with particular personas involved in the conflict, among them the Norwegian king Óláfr Tryggvason played the most significant role. The battle itself and its circumstances proved that Óláfr was a great, warlike, valiant and at the same time deeply Christian to do monarch, whose death was compared to martyrdom. The saga authors, thoroughly describing all events connected with the battle of Svoldr, included also Sigvaldi, the jarl of Jomsborg, in their narratives. According to most accounts, the jarl was member of coalition, Óláfr Tryggvason’s enemies, who planned to trap the Norwegian king, depriving him of life and power. Sigvaldi’s role was to pretend Óláfr’s friend and ally and lead him from Vindland, where he stayed, directly into trap. The saga authors created their narratives about Sigvaldi and his role in the events of the year 1000, quoting particular skaldic stanzas, which were used to corroborate their prose accounts. The analysis of these verses leads to conclusion that the saga authors felt completely free in using them, differently and very often mistakenly understanding their content. Particular stanzas, quoted in the saga narratives, analysed once more, seem in fact to refer to completely different persons and/or events, having nothing in common with either Sigvaldi or Óláfr Tryggvason’s last battle.